Review of under Frequency Load Shedding Program of Kosovo Power System based on ENTSO-E Requirements - Gazmend Kabashi; Skender Kabashi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Under-frequency load shedding (UFLS) is designed to protect the power system when the frequency drops below given thresholds by switching off certain amounts of the load aiming thus to balance generation and load. This paper presents a review of the existing UFLS (Under Frequency Load Shedding) program in compliance with recently revised Police-5 of Operational Handbook of ENTSO-e. The proposed review of the current UFLS program for Kosovo Power System has considered the main standards requirements and guidelines for UFLS set by ENTSO-E. This work examine system performance by conducting dynamic simulations of UFLS schemes subject to different imbalances between load and generation, and includes three power system island mode scenarios with different equivalent inertia of the system, respectively different size of the systems. With aim to define the best program of UFLS, which fits to the Kosovo Power System frequency behavior, two different UFLS programs are analyzed and results are compared. The proposed program is tested using a large scale PSS/E model which represents interconnected power system area of Southeast Europe.